Left-Behind Status and Bullying in Chinese Rural Children: The Roles of Parental Supervision and Support and Friends in Puppy Love - Liu, Qian (Journal of interpersonal violence, 2022)
Bullying behaviors, as exhibited by left-behind children (LBC) in China, occur commonly. Parental supervision and support, as well as friendship networks, have previously been verified as crucial aspects in determining the bullying behaviors of LBC. However, evidence of the interactive effect of these vital factors is sparse, and puppy love, which is inevitable among school-age children, is seldom investigated. The current study aimed to examine the roles of parental supervision and support as well as peers in puppy love in LBC bullying behaviors by means of a moderated mediation model. The data were derived from 28 counties/districts across China. We used data from the China Education Panel Survey (CEPS) of 3,252 junior high school students. A moderated mediation model was conducted by PROCESS procedure in Statistical Product and Service Solutions (SPSS) and the bootstrapping method was performed for inference test. The moderated mediation analysis showed that left-behind status was associated with bullying behaviors displayed by school-age students. Parental supervision and support mediated this association; furthermore, the mediation effects were dependent on the number of friends in puppy love. In particular, as the number of friends in puppy love increased, the mediating effect of parental supervision weakened, whereas the mediating effect of parental support became stronger. These results revealed the importance of parental support and supervision and peers in puppy love in shaping bullying behaviors among LBC. Future bullying prevention and intervention should promote parental supervision and support among LBC in rural China, especially those with many friends in puppy love.